Evaluación del efecto de biorvoss y amirvoss en baños de aspersión contra garrapatas en ganado bovino en la parroquia regulo de mora, Cantón San Miguel, Provincia de Bolívar. - García Romero, Anthony Joseph (2020)
The present investigation evaluates the different pharmacological combinations effects, in spray baths against ticks in cattle, in order to know the most effective treatment, the prevalence of ticks in the area and which are the most common anatomical regions of location of ticks; In addition to this, we seek to identify tick species according to their taxonomic classification and determine the presence of trace milk drugs in animals. With the use of a statistical model (DBCA) with 60 animals under study and a total of 3 treatments and 20 repetitions, in addition to an entomological study of the animals collected and liquid chromatography of the milk obtained from the animals under study. The treatment with the highest efficacy and external antiparasitic action was determined to be the pharmacological combination 2 that was treatment T3, presenting the highest efficacy against tick infestation. We were able to classify the presence of ticks of the genus (Boophilus microplus) as endemic, since we were able to establish 100% prevalence, and a genus of ticks (Boophilus microplus) was also obtained. The anatomical region of preference for the Boophilus microplus tick was established in the hindlimb due to the great musculature found in this area, in addition, another area that had great predilection was the abdominal region due to the great irrigation it presents. Through a chromatographic study, it was determined that no residues of Amitraz, Fipronil, Dichlorvos and Cypermethrin were found in raw milk from animals subjected to spray baths in the present investigation.